Struktur Dan Komposisi Vegetasi Mangrove Di Pulau Mantehage - Elok S. Putro; Johny S. Tasirin; Marthen T. Lasut; Martina A. Langi (COCOS, 2015)
ABSTRACTThis research was carried out from December 2012 to February 2013 at Mantehage Island. This research was aimed to describe the structure and composition mangrove vegetation at Mantehage Island. Mangrove ekosistem at Mantehage Island divided into seven segments according to the characteristic of the island. The methods used are plot sampling on systematic line. The results showed that mangrove in Mantehage concist of eleven species: Avicennia officinalis, Bruguiera gymnorrhiza, Bruguiera parviflora, Ceriops tagal, Excoecaria agallocha, Lumitzera littorea, Rhizophora apiculata, Rhizophora mucronata, Scyphiphora hydrophylla, Sonneratia alba, and Xylocarpus moluccensis. The highest importance value for tree were Bruguiera gymnorrhiza (97.33%), and Rhizophora apiculata (89.59%), for pole were Rhizophora apiculata (123.50%), and Rhizophora mucronata (70.59%), for sapling was Rhizophora apiculata (80.40%), and for seedling were Rhizophora apiculata (56.98%) and Bruguiera gymnorrhiza, (52.52%). At trees stratum, the segment D and E possessed higher species composition than other segments. The highest of frequency of occurance for trees were Bruguiera gymnorrhiza and Rhizophora apiculata.Key Words: Structure, Composition, Mangrove